Answer:
F= 0.44642857d+1
Step-by-step explanation:
Answer:
Sample mean weight = 808080 grams
Step-by-step explanation:
The number of samples, n = 161616
The mean weight, ![\mu = 808080](https://tex.z-dn.net/?f=%5Cmu%20%3D%20808080)
Standard deviation, ![\sigma = 555](https://tex.z-dn.net/?f=%5Csigma%20%3D%20555)
The sample mean weight,
= Mean weight, ![\mu](https://tex.z-dn.net/?f=%5Cmu)
Since ![\mu_{\bar{x}} = \mu](https://tex.z-dn.net/?f=%5Cmu_%7B%5Cbar%7Bx%7D%7D%20%3D%20%5Cmu)
Sample mean weight, ![\mu_{\bar{x}} = 808080](https://tex.z-dn.net/?f=%5Cmu_%7B%5Cbar%7Bx%7D%7D%20%3D%20808080)
Step-by-step explanation:
Given
w(x) = - 3x - 4
Now
w(7) = - 3 * 7 - 4
= - 21 - 4
= - 25
Hope it will help :)❤
Answer:
By closure property of multiplication and addition of integers,
If
is an integer
∴
is an integer
From which we have;
is an integer
Step-by-step explanation:
The given expression for the positive integer is x + x⁻¹
The given expression can be written as follows;
![x + \dfrac{1}{x}](https://tex.z-dn.net/?f=x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D)
By finding the given expression raised to the power 3, sing Wolfram Alpha online, we we have;
![\left ( x + \dfrac{1}{x} \right) ^3 = x^3 + \dfrac{1}{x^3} +3\cdot x + \dfrac{3}{x}](https://tex.z-dn.net/?f=%5Cleft%20%28%20x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%29%20%5E3%20%3D%20x%5E3%20%2B%20%5Cdfrac%7B1%7D%7Bx%5E3%7D%20%2B3%5Ccdot%20x%20%2B%20%5Cdfrac%7B3%7D%7Bx%7D)
By simplification of the cube of the given integer expressions, we have;
![\left ( x + \dfrac{1}{x} \right) ^3 = x^3 + \dfrac{1}{x^3} +3\cdot \left (x + \dfrac{1}{x} \right )](https://tex.z-dn.net/?f=%5Cleft%20%28%20x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%29%20%5E3%20%3D%20x%5E3%20%2B%20%5Cdfrac%7B1%7D%7Bx%5E3%7D%20%2B3%5Ccdot%20%5Cleft%20%28x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%20%29)
Therefore, we have;
![\left ( x + \dfrac{1}{x} \right) ^3 - 3\cdot \left (x + \dfrac{1}{x} \right )= x^3 + \dfrac{1}{x^3}](https://tex.z-dn.net/?f=%5Cleft%20%28%20x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%29%20%5E3%20-%203%5Ccdot%20%5Cleft%20%28x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%20%29%3D%20x%5E3%20%2B%20%5Cdfrac%7B1%7D%7Bx%5E3%7D)
By rearranging, we get;
![x^3 + \dfrac{1}{x^3} = \left ( x + \dfrac{1}{x} \right) ^3 - 3\cdot \left (x + \dfrac{1}{x} \right )](https://tex.z-dn.net/?f=x%5E3%20%2B%20%5Cdfrac%7B1%7D%7Bx%5E3%7D%20%3D%20%5Cleft%20%28%20x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%29%20%5E3%20-%203%5Ccdot%20%5Cleft%20%28x%20%2B%20%5Cdfrac%7B1%7D%7Bx%7D%20%5Cright%20%29)
Given that
is an integer, from the closure property, the product of two integers is always an integer, we have;
is an integer and
is also an integer
Similarly the sum of two integers is always an integer, we have;
is an integer
is an integer
From which we have;
is an integer.
Answer:
f(g(0)) = 45
Step-by-step explanation:
to evaluate f(g(0)) , evaluate g(0) then substitute the value obtained into f(x)
g(0) = - 3(0) - 3 = 0 - 3 = - 3 , then
f(- 3) = 2(- 3)² - 5(- 3) + 12
= 2(9) + 15 + 12
= 18 + 27
= 45